Natural Coagulants for Sustainable Wastewater Treatment: Current Global Research Trends - Nassani, DE; Alazaiza, MYD; Alzghoul, TM; Bashir, MJK (My University)
Natural coagulants have gained significant attention as effective agents for wastewater treatment, particularly in the removal of heavy metals. This study conducts a comprehensive bibliometric analysis of 268 publications over the past decade, aiming to assess research trends and developments in the application of natural coagulants in wastewater management. The analysis reveals a marked increase in publication output, with the number of articles rising from just five in 2015 to fifty-one in 2024, indicating a growing global awareness and investment in sustainable wastewater treatment practices. "Environmental science" emerges as the leading discipline, accounting for 31.3% of the total publications. Notably, Malaysia is identified as the foremost contributor, with 60 publications and 1149 citations, followed by India and Brazil, highlighting the robust research activity in these regions. The study identifies key natural coagulants, such as Moringa oleifera and chitosan, which are frequently cited for their efficacy in reducing heavy metal concentrations and improving overall water quality. Leading funding organizations, such as the Coordena & ccedil;& atilde;o de Aperfei & ccedil;oamento de Pessoal de N & iacute;vel Superior in Brazil, have significantly contributed to the growth of this field by financing numerous studies. Prominent journals, including the Journal of Environmental Chemical Engineering and Water Research, play a crucial role in disseminating research findings and advancing knowledge in this area. These publications are vital for sharing innovative methodologies and effective treatment solutions in the field of natural coagulants. Effective treatment methodologies identified in the literature include coagulation/flocculation and adsorption. The study highlights a variety of natural materials utilized for wastewater treatment, including plant-based coagulants derived from agricultural by-products, which not only address environmental concerns but also promote resource recovery.
Keywords: bibliometric analysis; eco-friendly processes; green chemistry